Hubungan Penguasaan Kosakata dengan Keterampilan Berbicara Siswa Kelas V SD Negeri 1 Tiuh Memon Kabupaten Tanggamus - Surastina Surastina; Frieska Maryova Rachmasisca (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
The problem obtained in this study is about speaking skills which are very influential on the mastery of vocabulary owned by students. Vocabulary as an element of language plays an important role in speaking activities. Students' interest in speaking lessons is still very low. This study aims to determine whether there is a relationship between vocabulary mastery and speaking skills. The research method used in this study is a quantitative research method through correlational studies. The population of this study were all fifth grade students of SD Negeri 1 Tiuh Memon, Tanggamus Regency, totaling 31 students. Instruments to collect data are speaking skill test, vocabulary mastery test. The analysis technique used is regression and correlation (simple, multiple). The results of the analysis show that there is a positive relationship between vocabulary mastery and speaking skills (rxy = 0.81 correlation coefficient was tested for significance by t-test obtained t count = 7.44 at the real level = 0.05 with n = 31 obtained t table = 2,045.